2019
DOI: 10.1002/brb3.1199
|View full text |Cite
|
Sign up to set email alerts
|

Association between miRNAs expression and cognitive performances of Pediatric Multiple Sclerosis patients: A pilot study

Abstract: Introduction The Pediatric onset of Multiple Sclerosis (PedMS) occurs in up to 10% of all cases. Cognitive impairment is one of the frequent symptoms, exerting severe impact in patients’ quality of life and school performances. The underlying pathogenic mechanisms are not fully understood, and molecular markers predictive of cognitive dysfunctions need to be identified. On these grounds, we searched for molecular signature/s (i.e., miRNAs and target genes) associated with cognitive impairment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…This gene is also a candidate for Schinzel-Giedion syndrome, a condition entailing severe developmental delay and occasional epilepsy ( Ko et al, 2013 ; Miyake et al, 2015 ). Likewise, STAB1 , which encodes a scavenger receptor for acetylated low density lipoproteins, with an important role in defending against bacterial infections, has been found to be associated with conditions impacting on our distinctive cognitive abilities, including bipolar disorder ( Witt et al, 2014 ), Alzheimer’s disease ( Giil et al, 2017 ), and pediatric Multiple Sclerosis patients ( Liguori et al, 2019 ). CASP7 encodes a caspase that contributes to the cleavage of nuclear substrates during neuronal apoptosis ( Hayashi et al, 2006 ).…”
Section: Genetic Signatures Of Domestication and The Genetics Of Wsmentioning
confidence: 99%
“…This gene is also a candidate for Schinzel-Giedion syndrome, a condition entailing severe developmental delay and occasional epilepsy ( Ko et al, 2013 ; Miyake et al, 2015 ). Likewise, STAB1 , which encodes a scavenger receptor for acetylated low density lipoproteins, with an important role in defending against bacterial infections, has been found to be associated with conditions impacting on our distinctive cognitive abilities, including bipolar disorder ( Witt et al, 2014 ), Alzheimer’s disease ( Giil et al, 2017 ), and pediatric Multiple Sclerosis patients ( Liguori et al, 2019 ). CASP7 encodes a caspase that contributes to the cleavage of nuclear substrates during neuronal apoptosis ( Hayashi et al, 2006 ).…”
Section: Genetic Signatures Of Domestication and The Genetics Of Wsmentioning
confidence: 99%
“…Research has consistently found that approximately one third of pediatric patients with MS suffer from neurocognitive impairment. This is somewhat less than what is typically reported in the adult literature, which ranges from 50% [21,22,23,24] to close to 70% [25,26]. Early diagnosis of cognitive dysfunction can be extremely important in POMS, given that physical status can be well preserved.…”
Section: Cognitive and Psychosocial Outcomesmentioning
confidence: 87%
“…Genetic risk factors and interactions between several risk factors (second-hand smoke, genetic predisposition, physical functioning) were also evaluated [119,120,121]. A recent pilot study [26] searched for genetic signatures associated with cognitive impairment in patients with POMS. They found that expressions of 11 miRNAs associated with cognitive test performance.…”
Section: Other Risk Factors Of Cognitive Impairmentmentioning
confidence: 99%
“…It is reported that protective miR-199a, pathogenic miR-320, miR-155, miR-142-3p and miR-142 are increased in MS lesions or peripheral blood mononuclear cells (PBMCs) [ 9 , 10 , 11 ]. On the other hand, miR-219, miR-34a, miR-103, miR-182-5p, miR-124 and miR-15a/b are decreased in the Cerebrospinal fluid (CSF), Tregs or PBMCs of MS patients [ 9 , 10 , 12 , 13 , 14 ]. There is a strong correlation between miRNAs and various manifestations of MS such as cognitive dysfunction and oxidative status, which can result in depression or fatigue [ 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%